The homilies of John Chrysostom on 1 Corinthians 12 : a model of Antiochene exegesis on the charismata - Stander, Hennie (Hendrik Frederik), 1953- (University of Pretoria, 2013)
Dissertation (MA (Ancient Languages and Cultures Studies))--University of Pretoria, 2007.